Organohalide respiration: retrospective and perspective through bibliometrics - Liao, Hengyi; Wang, Xuhao; Wang, Xin; Zhang, Manman; Zhang, Yiji; Huang, Siqi; Wang, Hongyan; Jin, Huijuan; Wang, Jingjing; Li, Xiuying; Yan, Jun; Schubert, Torsten; et al. (Frontiers in Microbiology, 2024)
Organohalide-respiring bacteria (OHRB) play a pivotal role in the transformation of organohalogens in diverse environments. This bibliometric analysis provides a timely overview of OHRB research trends and identifies knowledge gaps. Publication numbers have steadily increased since the process was discovered in 1982, with fluctuations in total citations and average citations per publication. The past decade witnessed a peak in publications, underscoring heightened research activity and extensive collaboration. Thematic analysis identified two primary research foci: mechanistic exploration of OHRB and their interplay with environmental factors. Future research should prioritize elucidating the roles OHRB’s play in biogeochemical cycling, utilizing synthetic biology tools for enhanced biotransformation, deciphering OHRB’s ecological interactions, unraveling their evolutionary pathways, and investigating dehalogenation capabilities in other microorganisms, including archaea. These research directions promise to advance our understanding of microbially-driven organohalide transformations, microbial ecology, and genetic engineering potential, ultimately informing natural organohalide cycling and environmental management strategies.